2010
DOI: 10.1007/978-3-642-15711-0_17
|View full text |Cite
|
Sign up to set email alerts
|

Nonlocal Patch-Based Label Fusion for Hippocampus Segmentation

Abstract: Abstract.Quantitative magnetic resonance analysis often requires accurate, robust and reliable automatic extraction of anatomical structures. Recently, template-warping methods incorporating a label fusion strategy have demonstrated high accuracy in segmenting cerebral structures. In this study, we propose a novel patch-based method using expert segmentation priors to achieve this task. Inspired by recent work in image denoising, the proposed nonlocal patch-based label fusion produces accurate and robust segme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 18 publications
(46 reference statements)
0
51
0
1
Order By: Relevance
“…In Coupé et al (2010Coupé et al ( , 2011b, we showed that accurate segmentations of anatomical structures can be obtained using this simple patch-based label fusion framework. In addition, to take advantage of the self-similarity of the image as done for denoising, the nonlocal label fusion also relies on intersubject anatomical consistency.…”
Section: Methods Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In Coupé et al (2010Coupé et al ( , 2011b, we showed that accurate segmentations of anatomical structures can be obtained using this simple patch-based label fusion framework. In addition, to take advantage of the self-similarity of the image as done for denoising, the nonlocal label fusion also relies on intersubject anatomical consistency.…”
Section: Methods Overviewmentioning
confidence: 99%
“…In Coupé et al (2010Coupé et al ( , 2011b, we were the first to introduce the nonlocal means estimator in the context of segmentation by averaging labels instead of intensities. By using a training library of N subjects, whose segmentations of structures are known, the weighted label fusion is estimated as follows: (3) where l(x s,j ) is the label (i.e., 0 for background and 1 for structure) given by the expert to the voxel x s,j at location j in training subject s. It has been shown that the nonlocal means estimator v(x i ) provides a robust estimation of the expected label at x i .…”
Section: Methods Overviewmentioning
confidence: 99%
“…The proposed Brain Extraction based on nonlocal Segmentation Technique (BEaST), is inspired by the patch-based segmentation first published in Coupé et al (2010) and extended in . As done in Coupé et al (2011), we use sum of squared differences (SSD) as the metric for estimation of distance between patches.…”
Section: Proposed Brain Extraction Methodsmentioning
confidence: 99%
“…A typical patch-based segmentation searches each region of the image to find the most similar patches within an atlas, a training database with known ground truth segmentation. The atlas is hence aligned with the image and a final segmentation is obtained by fusing the votes from selected patches of atlas images (Coupè et al, 2010;Rousseau et al, 2011).…”
Section: Brain Extractionmentioning
confidence: 99%